Urgensi Program Gerakan Literasi (GLS ) Untuk Meningkatkan Nilai Karakter Siswa Sekolah Dasar - Siti Komala Putri; Dinie Anggraeni Dewi; Rizky Saeful Hayat (LPPM Politeknik Pratama, 2024)
The School Literacy Movement (GLS) aims to improve the character values of elementary school students. Therefore, GLS needs to be in every school that is ready and has adequate facilities and infrastructure. Efforts to have a GLS program are in accordance with the policies conveyed by the Ministry of Education and Culture as stated in Minister of Education and Culture Regulation Number 23 of 2015 regarding tobligation to read literature for 15 minutes before the learning process begins. Literacy skills are not just reading or writing but also understanding the meaning of analyzing, criticizing and reflecting on what has been read. This means that literacy can improve a person's character. This research uses qualitative research, where the process of collecting data is qualitative and carries out literature studies or literature studies that look for data phenomena that are appropriate to the case or problem in the research. The findings in this research show that the GLS program has been implemented in several elementary schools, with a focus on improving character values which are now included in 21st century learning. Technology is increasingly developing rapidly. The existence of the GLS program is very helpful with stages that are in accordance with the Permendikbud guidelines so that the implementation of the program runs optimally and is supported by other parties.